Profile Of Retinoblastoma Patients At H. Adam Malik RSUP 2014-2017 - Dary Pallysater (Institute of Computer Science (IOCS), 2020)
Retinoblastoma is a malignant tumor disease of intraocular children. Retinoblastoma is caused by hereditary or non-hereditary factors. The general incidence of retinoblastoma is 1 in 15,000 births. Overall, more than two-thirds of retinoblastoma patients have unilateral tumors, the remainder have bilateral tumors. In Indonesia, the epidemiology of retinoblastoma is not known with certainty due to the lack of related research reports in the Indonesian population. The most common clinical presentation is leukocoria, followed by strabismus, pseudohypopyon, hyphema, orbital cellulitis, and vitreous hemorrhage. Aim. The purpose of this study was to determine the complete profile of retinoblastoma patients at Haji Adam Malik General Hospital in 2014-2017. Method. This research was designed in the form of a descriptive study with a retrospective research design. This research was conducted at Haji Adam Malik General Hospital. The population studied were retinoblastoma patients who were hospitalized at Haji Adam Malik General Hospital and the sample used was total sampling. The data collection method was carried out by collecting secondary data, namely medical records for the period January 2014 – July 2017, then processed with SPSS for Windows. Data analysis was carried out descriptively with frequency analysis. Results. The results showed that the incidence of retinoblastoma patients in the 2014-2017 period was 48 people, the 2-3 year age group was the largest age group (39.6%), good nutritional status was the largest group (52.1%), the most tumors were unilateral tumors. (91.7%)